La figuration du corps dans la mise en scène filmique du temps proustien - AZIZI-ZYSERMAN, Meriam (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
Representation of the Body in the Cinematographic Staging of Proust’ Vision of Time. Mainly of mental order, the proustian narrative resisted the visual transposition, in particular those passages of the text related to the reflection on the time led by the narrator-character and which become more marked in the last volume of La Recherche, where they are the main theme. Our purpose is to show how this resistance is diverted by the metaphor and the syllepse in The Prisoner by Chantal Akerman and The time regained by Raoul Ruiz and how these two stylistic operations preside over the body’s cinematographic figuration and participate, therefore, to the mise-en-scene of an unreal space. As consequence of a specific mise-en-scene, the body in the frame does no longer represent the character but obtains a symbolic function and becomes a temporal sign.